(untitled) (Journal of Economic Research & Business Administration, 2015)
Special economic zones are being created for the decision as external economic, and common economic issues of the country. In the industrially developed countries mainly the zones of the foreign type trade which are carrying out cargo handling operations with transit and acting on the territory of the country by the goods. Usually industrial activity here is carried out in the insignificant sizes and directed on external completion corresponding commodity markets. The main stimulus is customs privileges and canceling of the export-import control.